The ‘rural-urban’ mix in the use of prepositions and prepositional phrases by students of literature in Kenyan universities - Mbithi, Esther K. (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
The language of instruction at university level in the Kenyan education system is English, so all written work for assignments and examinations is generated in English. And yet, each student probably uses two or three languages in their everyday life in situations away from the classroom. Indeed, the language policy allows the use of mother tongue as language of instruction in Primary School classes One to Three. African languages are structured differently from the English language, particularly where prepositions are concerned. Furthermore, each language grows in a specific cultural context; and the range of vocabulary of the African languages in Kenya is different from that of English. This may present a challenge for university students using English as the language of instruction in understanding academic concepts for which there is no equivalent in their mother tongue. In some instances, only a single word is available in the first language, where several different English words are possible or even necessary for clarity depending on the context. This paper explores this cultural peculiarity of linguistic marginalisation, which is both lexical and syntactic, as manifest in the written research papers of university literature students who would otherwise work simultaneously in different languages.